THE ASSOCIATION OF THE POLYMORPHISM AND GENE EXPRESSION OF HEAT SHOCK PROTEIN HSP70 GENE IN WINTER AND SUMMER IN THE SEMEN OF HOLSTEIN BULLS BORN IN IRAQ - Hassan Nima Habib; Bassam Yasein Khudaier; Amad Falah Hassan; Wessam M M Saleh (Basrah Journal of Veterinary Research)
The HSP70 protein considered as a molecular markers to resist various stressconditions, especially high temperatures. Therefore, the high level of gene expressionof hsp70 gene is one of the ways to resist stress conditions, which can vary dependingon the polymorphisms. The study aimed to determine the extent of the correlationbetween gene expression and polymorphisms to hsp70 gene. The study was conductedin the months: November , December , 2015, January 2016, as the winter season andthe months April , May and June, 2016, as the summer season. Twenty nine Holsteinbulls born in Iraq of known fertility, 2.5 – 3.5 years old, back to ArtificialInsemination Center of Abou-Ghareeb Baghdad, Iraq, the General Company forLivestock Services, Semen collected using artificial vagina method, mRNAextraction, Synthesis of mRNA to cDNA and Real-Time Quantitative RT–qPCR weredone. The results showed significant differences in the level of gene expressionbetween polymorphisms to the hsp70 gene. In conclusion there is a positivecorrelation between the gene expression and polymorphisms of hsp70 gene inHolstein bulls born in Iraq .